OPTIMALISASI PEMANFAATAN DAN DIVERSIFIKASI OLAHAN PANGAN LOKAL SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Kurniyati, Yuli; Rahmawati, Fitri; Suryati, Pulut (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The purpose of this activity is the program: (1) increasing knowledgeabout the members of KWT good food and a variety of local food processing;(2) improve the skills of the local food processing production process;(3) improve the skills and knowledge of the packaging and labeling of interest;(4) increasing knowledge about the ins and outs of administrative partnerKWT; (5) improve knowledge of financial management and sales pricecalculation method; (6) motivate and increase knowledge of productivebusiness activities (entrepreneurship); and (7) increase knowledge of marketingthrough the internet .The method used in this service activity is socialization, training, andmentoring.The results of this activity is the increased knowledge, understandingand skills of participants in the field of diversified local food processingand the production of local food processing, packaging and labeling ofinterest, KWT administration, business financial management, entrepreneurship,and marketing through the internet, it is seen from indicators: (1) membersKWT producing snacks (snack) to be deposited into the stalls; (2) setup shop Romadhon; (3) completion of the financial administration of the organizationand administration of KWT; (4) the creation of KWT stalls as amember of the marketing group produki; (5) blog KWT as media marketingon line and card-making nama; (6) snack orders increase for members ofKWTKeywords : diversification, local food, and processing